Synthesis and characterization of rubidium-containing bioactive glass nanoparticles - Ouyang, Sihui; Zheng, Kai; Huang, Qianli; Liu, Yong; Boccaccini, Aldo R. (Materials Letters, 2020)
Developing bioactive glass nanoparticles (BGNs) comprising biologically active ions is a promising strategy to enhance therapeutic performance. Given the pro-osteogenic activity of rubidium (Rb), a new type of Rb-containing BGNs was developed in this work. Here, a modified Stӧber method was employed to synthesize monodispersed spherical BGNs (particle size 100 nm) with different contents of Rb incorporation (nominal 1, 3 and 5 at.%). The results showed that Rb incorporation did not significantly affect the size, shape and amorphous characteristic of BGNs. The real Rb contents (maximum 0.62 at.%) in BGNs were much lower than the designed ones. Compared with Rb-free BGNs, Rb-BGNs exhibited enhanced hydroxyapatite-forming ability in simulated body fluid. The results suggest that Rb-BGNs are promising to be used as bioactive fillers for bone regeneration applications.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bioceramics; Bone regeneration; Nanoparticles; Rubidium; Sol-gel preparation